STRATEGIC ECONOMIC PARADIGMS IN THE FOURTH INDUSTRIALREVOLUTION: A MULTIDIMENSIONAL ANALYSIS OF POLICY, TECHNOLOGY, AND SOCIO-ECONOMIC DYNAMICS - Rusmiyati Rusmiyati; Iwan Harsono; Henny Noviany; Evie Farida Juliarta; Kartijo (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study conducts a comprehensive analysis spanning various dimensions to unravel the intricacies of strategic economic paradigms within the Fourth Industrial Revolution (4IR). The research delves into the dynamic interplay of policy, technology, and socio-economic factors, aiming to discern the multifaceted challenges and opportunities arising from disruptive innovations characterizing the 4IR era. By synthesizing insights from diverse perspectives, the study provides an in-depth understanding of the complex economic landscape shaped by transformative technologies such as artificial intelligence, blockchain, and the Internet of Things. It emphasizes the necessity for adaptive strategies in policymaking to address the rapidly evolving nature of economic paradigms. Furthermore, the research identifies key challenges and explores potential pathways for informed decision-making in navigating the complexities of the 4IR. By exploring disruptive innovations and their impact on economic structures, the study aims to contribute valuable insights for policymakers, researchers, and stakeholders. This analysis is a foundational resource for those seeking to foster sustainable economic development, promoting Resilience and adaptability in the face of unprecedented technological change.